Gamma delta T-cell receptor repertoire in acute multiple sclerosis lesions. - Wucherpfennig, K W (1992)
Gamma delta T cells are a distinct lymphocyte population that can exhibit reactivity with heat shock proteins over-expressed at inflammatory sites. As gamma delta T cells may be involved in the central nervous system (CNS) inflammatory process in multiple sclerosis (MS), we examined T-cell populations in MS plaque tissue by quantitative immunohistochemistry and sequence analysis of T-cell antigen receptor (TCR) delta chains. Gamma delta T cells that express the variable (V) gene segments V delta 1, V delta 2, and V gamma 2 (V gamma 9) were found to accumulate in acute, demyelinating MS plaques and appeared to have undergone clonal expansion, most likely because of recognition of a specific CNS ligand. Further, 60-kDa and 90-kDa heat shock proteins (hsp60 and hsp90), which may be target antigens for autoreactive gamma delta T cells, were found to be expressed in normal CNS tissue and overexpressed in acute MS plaques. In acute plaques, hsp60 was found in foamy macrophages, while hsp90 was detected in reactive astrocytes. These results provide evidence for a role of gamma delta T cells in active stages of MS.